Human CD26high T cells elicit tumor immunity against multiple malignancies via enhanced migration and persistence - Stefanie R. Bailey (Nature Portfolio, 2017)
The role of human CD4+ T cell subsets in cancer immunotherapy is still unclear. Here, the authors show that CD26 identifies three CD4+ T cell subsets with distinct immunological properties in both healthy individuals and cancer patients.